Enhancing Quranic Literacy in Elementary Education: The Efficacy of Problem-Based Learning in Teaching Surah At-Tin - Setiyono (Jurnal Keprofesian Guru Keagamaan, 2025)
This study aims to describe the application of the Problem-Based Learning (PBL) model and analyze the improvement in student learning outcomes on the material “Let's Learn the Qur'an Surah at-Tin” in grade V of SD Negeri 004 Sedarat Baru. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was carried out in three cycles, each consisting of planning, action, observation, and reflection stages. The research subjects included 12 fifth-grade students (7 boys and 5 girls). Data were collected through observation and learning outcome tests at the end of each cycle. The results showed that the application of the PBL model significantly improved students' memorization skills. This was evidenced by an increase in the percentage of student learning completeness (KKM) from 25% in the pre-cycle stage to 42% in cycle I, increasing to 67% in cycle II, and reaching 92% at the end of cycle III. The implications of this study indicate that the PBL model is effective in increasing student activity and cognitive achievement in Islamic Religious Education and Ethics subjects, so that it can be used as a reference for teachers in developing teaching variations in the classroom.